An unexpected encounter: educational science and psychoanalysis in the phenomenological pedagogy of Piero Bertolini - Elisabetta Biffi (University of Bologna, 2016)
The present paper offers a reflection on the interconnections between pedagogy and psychoanalysis as interpreted in the phenomenological pedagogy of Piero Bertolini. Interest in the topic is justified by the fact that throughout his work (especially in Bertolini, 1988; 2005) this author himself repeatedly argued for the existence of such links. In the current paper, I outline and analyse some key points of intersection between phenomenological pedagogy and the psychoanalytical perspective. Specifically, I examine the theoretical bases justifying a comparison of these two sciences, the core thematic affinities between them, and finally the implications for the practice of phenomenological pedagogy that arise from this interdisciplinary encounter.